(untitled) (Journal of Engineering, 2009)
The performance of thermal storage porous wall with vents (gravel material) is analyzed for passive solar heating system under Baghdad climatic conditions by comparing it with conventional wall (Concrete wall) for a variety of control strategies. The variation has been calculated during a period of heating season for three months from December (1999) to February (2000) by using computer simulation with MATLAB language (Ver.6.5). A mathematical model containing the governing differential equations of heat transfer through the wall and glazing under unsteady heat flow was performed by using “control volume” technique to obtain the temperature distribution within the wall. The study was carried out for a south facing vertical wall and the effect of different thicknesses, porosities, effect of insulation and glazing layers and effect of vents was also investigated